ELEVATED LP(A) IS A RISK FACTOR FOR PREMATURE ISCHAEMIC HEART DISEASE IN A MULTI-ETHNIC COHORT - Loh, Wann Jia; Simon, Oliver; Yeo, Colin (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Elevated plasma lipoprotein(a) [Lp(a)] is a common inherited condition independently associated with ischaemic heart disease (IHD). A Mendelian randomisation study recently suggested that elevated plasma Lp(a) concentrations confer a similar causal risk as heterozygous familial hypercholesterolemia for premature IHD. METHODOLOGY This study was a cross-sectional analysis aimed to assess whether elevated Lp(a) concentrations were associated with premature IHD in a South-East Asian cohort. Plasma Lp(a) levels were measured in consecutively recruited patients with IHD who were admitted to the hospital. Information on the age of diagnosis of IHD and the presence of comorbidities at the time of initial diagnosis of IHD were obtained from history taking and electronic medical records. Premature IHD was defined as IHD diagnosed <45 years of age for males and <50 years for females. The relationship was examined by regression model adjusting for age, gender, ethnicity, diabetes, hypertension, hyperlipidaemia and smoking. RESULTS Of the total of 521 patients included, 82.2% were male, 46.5% were newly diagnosed with IHD, and 9.5% had premature IHD. The median age was 63.4 years while the median age of onset of IHD was 59.2 years. Our multi-ethnic cohort included Chinese (49.3%), Malay (31.3%), Indian (12.7%) and other (6.7%) ethnicities. The Lp(a) distribution was positively skewed to the right for all ethnicities. At the 90th and 95th percentiles, Lp(a) concentrations were 155 nmol/L and 195 nmol/L, respectively. Univariable and multivariable regression analysis identified Lp(a) ≥155 nmol/L to be associated with premature IHD. CONCLUSION Elevated Lp(a) was associated with premature onset of IHD in our multi-ethnic cohort. Lp(a) levels should be routinely measured in all individuals with established or at high risk for IHD. More studies are required to evaluate the Lp(a) threshold that would be clinically useful to identify individuals at risk for premature IHD.